Non-sequential double ionization of Ar: from the single- to the many-cycle regime - Kübel, M.; Betsch, K. J.; Kling, Nora G.; Alnaser, A. S.; Schmidt, J.; Kleineberg, U.; Deng, Y.; Ben-Itzhak, I.; Paulus, G. G.; Pfeifer, T.; Ullrich, J.; Moshammer, R.; et al. (My University, 2014)
The transition from the near-single to the multi-cycle regime in non-sequential double ionization of argon is investigated experimentally. Argon atoms are exposed to intense laser pulses with a center wavelength around 790 nm and the momenta of electrons and ions generated in the double ionization process are measured in coincidence using a reaction microscope. The duration of the near transform-limited pulses is varied from 4 to 30 fs. We observe an abrupt collapse of the cross-shaped two-electron momentum distribution [17] in the few-cycle regime. The transition to longer pulses is further accompanied by a strong increase in the fraction of anti-correlated to correlated electrons.